Impact of alcohol and smoking cessation on the course of chronic pancreatitis - Göltl, Philipp; Murillo, Katharina; Simsek, Onur; Wekerle, Maximilian; Ebert, Matthias; Schneider, Alexander; Hirth, Michael (Alcohol, 2024)
Objectives - Alcohol and nicotine are the two most important risk factors of chronic pancreatitis, and they often occur together. It is still unclear how much they influence the severity of the disease and which of the two addictions should be treated with priority. - Methods - We performed a single-center, retrospective, cross-sectional study in a mixed medicosurgical cohort of 870 patients diagnosed with chronic pancreatitis (CP). We analyzed the impact of the drinking pattern and abstinence for alcohol and nicotine on the course of the disease. Patients with alcoholic CP were subdivided into 1) patients with “life-time drinking history” (LTDH), 2) “current drinkers” with current alcohol abuse without signs of LTDH, and 3) “former drinkers” who stopped or reduced alcohol intake dramatically. - Results - Compared to patients with LTDH, “former drinkers” had a lower rate of exocrine insufficiency (29% vs. 59%) and pseudocysts (33% vs. 49%), were more often relapse-free (37% vs. 5%), and had less abdominal pain. There was no correlation detected between the quantity of alcohol consumption and the severity or progression of the disease. Regarding nicotine, 29 pack-years are the threshold for developing the early stage of CP. Under nicotine abstinence, only slightly more patients were relapse-free (37% vs. 22%). In contrast, the cumulative amount of nicotine consumed correlated with overall disease severity and the development of pseudocysts. The need for surgery was increased, with odds ratios of 1.8, for both alcohol and nicotine abuse. - Conclusions - Alcohol cessation in chronic pancreatitis reduces exocrine insufficiency, abdominal pain, and local complications. The effect of nicotine cessation is less pronounced in our cohort. However, nicotine abuse represents an important factor for the development of the disease.